Energy harvesting from a piezo buzzer with Schottky diode and complementary MOSFET full-bridge rectifiers - Gogoi, Niharika; Kirchner, Jens; Fischer, Georg (2022 IEEE International Symposium on Applications of Ferroelectrics (ISAF), 2022)
In our paper, we have taken advantage of human walking on piezoelectric element and rectified the generated voltage through two types of rectifiers: standard rectifier (SR) and complementary MOSFET rectifier (CMOS-R). For a symmetric voltage signal, CMOS rectifier has always been a better choice than any diode based rectifier. However, in our work, it was observed that the SR gave higher output voltage levels than the CMOS-R <br
Keywords: PZT; energy harvesting circuit; rectifier